Corazón Abierto : Mexican American Voices in Texas Music - Hudson, Kathleen, 1945- (Book collections on Project MUSE., 2022)
"Corazón abierto: Mexican American voices in Texas music provides a wide view of the myriad contributions Mexican American artists have made to music in Texas and the United States. Based on interviews with longtime stalwarts of Mexican American music -- Flaco Jimenez, Tish Hinojosa, Ernie Durawa, Rosie Flores, and others -- and also conversations with newer voices like Lesly Reynaga, Marisa Rose Mejia, Josh Baca, and many more, Kathleen Hudson allows the musicians to tell their own stories in a unique and personal way. As the artists reveal in their free-ranging discussions with Hudson, their influences go far beyond traditionally Mexican genres like conjunto, norteño, and Tejano to extend into rock, jazz, country-western, zydeco, and many other styles. Hudson's survey also includes essays, poetry, and other creative works by Dagoberto Gilb, Sandra Cisneros, and others, but the core of the book consists of what she describes as 'a collection of voices from different locations in Texas. . . . Some represent voices from the edge, while others give us a view from the center.' Weaving together a tapestry that combines 'family, borders, creativity, music, food, and community,' the book presents an image as varied and difficult to define as the musicians themselves. By sharing the artists' accounts of their influences, their experiences, their family stories, and their musical and cultural journeys, Corazón abierto reminds us that borders can be gateways, that differences enrich, rather than isolate"--